2017
DOI: 10.1021/jacs.7b10360
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of van der Waals Adsorption on the Metal–Organic Framework NU-1000 with Zr6-oxo, Hydroxo, and Aqua Nodes

Abstract: We report measurements of adsorption isotherms and the determination of the isosteric heats of adsorption of several small gases (H, D, Ne, N, CO, CH, CH, Ar, Kr, and Xe) on the metal-organic framework (MOF) NU-1000, which is one of the most thermally stable MOFs. It has transition-metal nodes of formula Zr(μ-OH)(μ-O)(OH)(OH) that resemble hydrated ZrO clusters and can serve as catalysts or catalyst supports. The linkers in this MOF are pyrenes linked to the nodes via the carboxylate groups of benzoates. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 49 publications
4
32
0
Order By: Relevance
“…In the case of NU-1000, we consider coordination only to "c pore" active sites since as shown in our previous study, 38 the c pores are more active than the large pores in this MOF presumably due to the existence of rather strong dispersion like interactions in the narrower c pores than the large ones. This also agrees with recent studies reporting larger heats of adsorption for small substrates 65 as well as selective precursor deposition in atomic layer deposition 66,67 in the c pores of this MOF. We further consider monoand bi-defective UiO-66 as well as mono-, bi-and tetradefective Zr12 MOFs.…”
Section: Number and Morphology Of Missing Linker Defects In Singlevs supporting
confidence: 93%
“…In the case of NU-1000, we consider coordination only to "c pore" active sites since as shown in our previous study, 38 the c pores are more active than the large pores in this MOF presumably due to the existence of rather strong dispersion like interactions in the narrower c pores than the large ones. This also agrees with recent studies reporting larger heats of adsorption for small substrates 65 as well as selective precursor deposition in atomic layer deposition 66,67 in the c pores of this MOF. We further consider monoand bi-defective UiO-66 as well as mono-, bi-and tetradefective Zr12 MOFs.…”
Section: Number and Morphology Of Missing Linker Defects In Singlevs supporting
confidence: 93%
“…MOFs can be designed for desired separation and capture processes by tuning the microporous channels and introducing functional groups. There are several pyrene-based MOFs in the literature that have been investigated for adsorption and separation owing to different reasons, such as (i) preferential binding sites on the carboxylates and aromatic rings on the linker, 90,195 (ii) permanent porosity and framework stability in the presence of water, 78 (iii) suitable pyrene-pyrene distance for the adsorption and separation of gas molecules, 57,77,85 (iv) the presence of rotatable units connected to pyrene ligand, resulting in enhanced loading of the guest molecules in the structure, 60 (v) donor-acceptor interaction between the adsorbate molecule and pyrene, 91 and (vi) the possibility of using functional groups within the MOF as structure-directing agents. 84 In this section, we will discuss pyrene-based MOFs that have been investigated for adsorption and separation of different molecules and Table 4 will be summarizing all the performances.…”
Section: Adsorption and Separation Of Moleculesmentioning
confidence: 99%
“…[275] In the same way, the importance of van der Waals forces for the adsorption of small gases can be predicted and used for practical application. [276] The dimension of guest and host pore is often a neglected topic. Theoretically, the minimum and maximum projection diameter of a guest can be easily calculated and compared to channel, cage and window size of reticular materials but a huge number of practical examples show that reticular materials are more flexible.…”
Section: Mofs Cofs and Zifs-host-guest Interaction Practical Examplesmentioning
confidence: 99%
“…Theoretically, the minimum and maximum projection diameter of a guest can be easily calculated and compared to channel, cage and window size of reticular materials but a huge number of practical examples show that reticular materials are more flexible. [276] It could be demonstrated that even a protein (cytochrome c) can enter in the interior of an MOF despite the larger dimension compared to the pore size. [277] On the other hand the pore dimension can be used to selectively sieve different guest molecules.…”
Section: Mofs Cofs and Zifs-host-guest Interaction Practical Examplesmentioning
confidence: 99%
See 1 more Smart Citation